Evaluation and Analysis of Literature for COVID-19 and Climate Change - Chatzara, Eirini; Apostolia Galani; Arhonditsis, George; Evangelia Mavrikaki (Re-visioning Geography: Supporting the SDGs in the post-COVID era, 2023)
The COVID-19 pandemic really went viral (pun intended) and dominated the media and public discourse, often overshadowing coverage of the equally urgent climate crisis. Despite their distinct features, both crises share important characteristics, such as global impact, economic repercussions, and associations with biodiversity loss, which disproportionately affect marginalized communities. Based on the bibliometric analysis, a significant body of literature exists on the impact of climate change on virus transmission and the environmental consequences of the pandemic. This work focuses on articles that explore the COVID-19 crisis as a learning experiment for the climate crisis, suggesting that in both cases, mitigation policies are less costly than adaptation policies, a collective global response should be agreed upon through international agreements, support for vulnerable communities is crucial, and effective communication to policymakers and the public is paramount.